Education on Electromagnetic Waves Exposure from Smart Devices in Elementary School - Kusumawardhani, Eka; Putra, Leonardus Sandy Ade; Nugraheni, Putranty Widha; Tarbiyatun Nasyin Maleiva, Lalak; Wicaksono, Romario Aldrian (International Journal of Community Service Learning, 2023)
Advances in science and technology are increasingly sophisticated and complex. Smart devices, smartphones, tablets, and other complicated media mark the rapid development of communication technology. Smart devices are electronic devices, generally connected to other devices or networks via different wireless protocols. One example of a smart device that is widely used is a smartphone. People frequently use smartphones as a communication tool in the current global era. As a result, most people are dependent on these devices, which can expose them to harmful electromagnetic waves. Given the dangers smartphones can cause to people, it is recommended to limit the use of smartphones. Therefore, the purpose of implementing this community service is to educate the public, especially students and teachers at SDN 16 Bekut, on the dangers of smartphone radiation. This is done by educating people about the need to use smartphones responsibly and not excessively. Based on the questionnaire results and recapitulation of the results of this activity, it was found that the level of understanding and satisfaction index of the actifvity participants reached 86.45%.